Dr Pelatihan Surveilans Vektor Malaria di Desa Banyuasin, Kecamatan Loano, Kabupaten Purworejo - Muh, Fauzi; Martini, Martini; Hestiningsih, Retno; Setyawan, Henry; Kusariana, Nissa; Udijono, Ari (Poltekkes Kemenkes Surakarta, 2026)
Background: Malaria remains a significant public health challenge in Purworejo Regency, Central Java Province, Indonesia, with persistent transmission despite various preventive measures This community services aimed to improve community health center (puskesmas) cadres’ knowledge of malaria transmission and their practical skills in identifying breeding sites, vector surveillance, and environmental management. Methods: This community engagement initiative aimed to enhance the knowledge and skills of community health center (puskesmas) cadres in identifying malaria vectors and conducting mosquito habitat surveys. The project involved 28 cadres from puskesmas across Purworejo Regency and was conducted in Banyuasin Village, Loano Subdistrict. The intervention consisted of educational sessions on malaria basics and mosquito identification, followed by hands-on training in field-based habitat survey techniques. Pre- and post-tests were administered to assess the effectiveness of the training. Results: Descriptive analysis revealed a significant improvement in participants’ knowledge following the intervention. The mean score increased from 22.1 before the training to 28.8 after the training, with the difference being statistically significant (p < 0.05, paired samples t-test). Conclusion: The findings suggest that community-based education and capacity-building initiatives, involving the direct participation of community members and health cadres, can effectively improve awareness and knowledge related to malaria control. The findings suggest that community-based education and capacity-building involving community members and health cadres can improve malaria awareness and knowledge, and sustained implementation with collaboration among local government, public health institutions, and the community is essential for understanding malaria risks, promoting preventive practices, and ensuring sustainable control efforts.